THE INFLUENCE OF TAX AVOIDANCE AND PROFIT MANAGEMENT ON THE VALUE OF COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Cahya, Nilam; Semaun, Syahriyah; Purnamasari, Rini (Institut Agama Islam Negeri Parepare, 2024)
This research aims to determine the relationship between tax avoidance and earnings management on company value. Tax avoidance is considered a flow of wealth from the government to the company, which should increase the value of the company. This research was conducted to test whether there is an influence of Tax Avoidance and Profit Management on the Company Value of 15 companies that have become constituents of the Indonesian Stock Exchange during 2020-2022. This research uses associative quantitative methods with data collection techniques in the form of documentation using secondary data, and processing using SPSS version 26. The data analysis techniques for this research are classical assumption testing, multiple regression analysis, and hypothesis testing. The research results obtained show 1) Tax avoidance does not partially have a significant influence on company value. This is proven by the t-test carried out, where the calculated t value (0.37) < t table (2.01) and a significant value of 0.71 are obtained. > 0.05. 2) Earnings management has no significant influence on company value. This is proven by the t-test carried out, where the calculated t value was obtained (-0.05) < t table (2.01) and a significant value of 0.93 > 0.05. 3) Simultaneously Tax District, Pinrang Regency, as evidenced by the Pearson correlation value of 0.564, meaning that the two variables have a moderate correlation with a positive relationship. Financial Management Behavior influences Financial Well-Being, this is proven by the calculated t value > t table or 6.694 > 1.985 with a significance of 0.00 < 0.05.